Traditionliliyan as Social Capital of the Tidore Community - Putri Nurdiana Jailan (Peneliti.net, 2023)
Research entitled TraditionLiliyan As Social Capital for the Tidore community, it is a response to the community's need for help for those in need as a basic foothold in society. Research related to TraditionLiliyan This is considered urgent to do because in implementation it has the power of social capital which has the principle of enormous benefit for the people of Tidore, such as preventing structural poverty, preventing social disintegration, preventing conflict and several other benefits which are considered important to be expressed and published so that the spirit of social life for The community is getting stronger, because implementing this tradition contains enormous social capital power.